Where do we stand with "whatever it takes"? - Karl Whelan (University College Dublin, UCD School of Economics, 2022)
It is ten years since Mario Draghi's "whatever it takes" speech and the announcement of the OMT programme designed to address financial fragmentation. This paper reviews the sources of financial fragmentation including and discusses whether monetary tightening over the next few years will trigger concerns about unsustainable fiscal burdens in some euro area member states. The paper discusses the evolution of ECB policy regarding fragmentation and the practical and legal issues involved. Legal limits on sovereign bond holdings may force the ECB into some difficult choices in the coming years.
Keywords: 330